Tarımsal Sürdürülebilirlikte Yeni Yaklaşımlar - Rezaee Danesh, Younes; Yazarel, Serkan; Şirin, Ünal; Karaman, Sedat; Furan, M. Alp; Genli, Gülistan; Hatipoğlu, Mürşide; Erdinç, Çeknas; Erkuş, Fatih Şevki; Çelikyürek, Hasan; Çelikyürek, Burak Egemen; Uyak, Cüneyt; et al. (2023)
-